Visual resolution and spatial performance: the trade-off between resolution and interactivity - Smets, G.J.F.; Overbeeke, K.J. (Virtual Reality Annual International Symposium, 1995 (VRAIS '95, 1995)
A series of experiments is reported in which subjects performed a search-and-act spatial task in conditions of reduced resolution and exploratory freedom. Images were produced using miniature cameras, comparing static camera position, passive camera movement, and head-coupled immersive VR/teleoperation conditions. By using cameras and real light, time lags could be avoided. Video processors were used to artificially reduce spatial, and temporal resolutions. Results show that although spatial and intensity resolutions are very important in static viewing conditions, like those of traditional image-producing computer graphics, subjects can complete the puzzle in head-mounted (VR-like) conditions with resolutions as little as 18/spl times/15 pixels. Furthermore results show that animation of the image viewpoint does not always improve spatial performance when the animation is not user-controlled; in some conditions performance actually got worse by adding passive movement.